Edukasi Dan Pemeriksaan Penyakit Kusta Dan Frambusia Di RT 27 Dusun Besar Wilayah Kerja Puskesmas Jembatan Kecil - Ida Samidah; Murwati Murwati; Danur Azissah R. Sojais; Jipri Suyanto; Emi Pebriani; Sulastri Sulastri; Wemi Royana; Elpina Elpina (Universitas Dehasen Bengkulu, 2023)
Leprosy (morbus hansen) is a chronic chronic infectious disease caused by Mycobacterium leprae (M.leprae) which attacks almost all organs of the body, especially the peripheral nerves and skin and other organs such as the oral mucosa, upper respiratory tract, reticuloendothelial system, eyes. , muscles and bones except the central nervous system. Yaws is a chronic infectious disease caused by Treponema pallidum subspecies pertenue which occurs in the tropics, especially in densely populated areas, low socio-economic, and poor hygiene). Measurement activities with the theme Education and Examination of Leprosy and Yaws in Rt 27 Dusun Besar Working Area of the Jembatan Kecil Health Center with the aim of increasing knowledge and early detection of Leprosy and Yaws. The community service activities that have been carried out are considered very important so that the community can recognize and detect leprosy and yaws early and get treatment immediately. Community service participants were able to briefly explain leprosy and yaws. The community service participants were enthusiastic about the activities carried out to increase knowledge in the form of education about leprosy and yaws. The participants were very happy to participate in the examination of leprosy and yaws